Assessment of the anti‐hyperalgesic efficacy of J‐2156, relative to clinically available analgesic/adjuvant agents in a rat model of mild to moderate chronic mechanical low back pain (LBP). (4th August 2020) - Kuo, Andy; Lourdesamy, Jacintha; Nicholson, Janet R.; Corradini, Laura; Smith, Maree T.
Abstract: Chronic mechanical low back pain (cLBP) is a leading cause of disability and a major socio‐economic burden internationally. The lifetime prevalence of non‐specific LBP is approximately 84%, with the prevalence of cLBP at about 23%. Clinically available analgesic/adjuvant medications often provide inadequate pain relief in patients experiencing cLBP. Hence, the urgency for discovery of effective and better tolerated medications. Fourteen days after the induction of five shallow annular punctures (5X) in the lumbar intervertebral discs at L4/L5 and L5/L6 in male Sprague‐Dawley rats, mechanical hyperalgesia was fully developed in the lumbar axial deep tissues at L4/L5 (primary) and L1 (secondary). Importantly, mechanical allodynia in the hindpaws was absent. From day 28, we assessed the face validity of our mild to moderate LBP‐5X rat model using four clinically available analgesic/adjuvant drugs, namely gabapentin, morphine, meloxicam and amitriptyline relative to vehicle. Additionally, the anti‐hyperalgesic effects of J‐2156, a highly selective small molecule somatostatin type 4 receptor agonist was assessed. Single i.p. bolus doses of gabapentin and meloxicam at the highest doses tested (100 and 30 mg/kg, respectively) alleviated secondary hyperalgesia (L1) but not primary hyperalgesia (L4/5). Morphine at 1 mg/kg alleviated both primary and secondary hyperalgesia in these tissues, whereas amitriptyline at the doses tested, lacked efficacy. These findings attest to the face validity of our model. J‐2156 at 10 and 30 mg/kg alleviated secondary hyperalgesia in the lumbar axial deep tissues at L1 with a non‐significant trend for relief of primary hyperalgesia in the corresponding tissues at L4/L5 in these animals. Abstract : Single doses of gabapentin, morphine, meloxicam and J‐2156 alleviated secondary hyperalgesia (2° H) in the rat model of mild to moderate low back pain (LBP‐5X). Morphine is the only drug that was effective in relieving both 2° H and primary hyperalgesia (1° H). By contrast, amitriptyline was ineffective.